From Grammatical Knowledge to Communicative Use: An Applied Study of Linguistic Competence among Libyan EFL University Learners (Comprehensive Journal of Science, 2026)
This study investigates the relationship between grammatical knowledge and communicative competence among Libyan university learners of English as a Foreign Language (EFL). Although learners often acquire formal grammar rules in classroom settings, they struggle to apply this knowledge in real communicative contexts   a discrepancy that reflects a gap between linguistic competence and communicative ability. Drawing on theoretical foundations that distinguish between knowing about language structure and using language appropriately in interactions, this research explores the degree to which grammatical competence predicts communicative performance in EFL settings. A mixed‑methods design was employed, combining grammar tests with communicative tasks and learner interviews. Findings reveal a moderate correlation between grammatical accuracy and communicative use, highlighting roles of sociolinguistic awareness and pragmatic strategy use. The study concludes with pedagogical implications for English language teaching in Libya, advocating integrative instructional approaches that balance structural accuracy with purposeful communication.
Keywords: Grammatical knowledge, Communicative competence, Linguistic competence, EFL learners, Libya